PEMBUATAN MULTIMEDIA COMPANY PROFILE CV. SARANA WIJAYA SEBAGAI MEDIA INFORMASI - Edy Siswanto; Robby Andika Kusumajaya; Nining Fitriani (MANAJEMEN, 2021)
Sarana Wijaya is a limited liability company for the procurement of construction goods and services founded by Mr. Tri Pudjiarso and Mrs. Anik Purwamti. On December 21, 2009 in Semarang CV. Sarana Wijaya is located at Jl. West Cinde 9 No. 15 Semarang.The purpose and objective of this company is to run a business that is engaged in establishing and operating companies in the construction of buildings, housing, bridges, roads, railways, dams, reclamation, dredging, docks, drainage, and landscaping. (landscaping) and interior design.The research methodology used by the author is desriptive research type and the research specifications used by the author are descriptive qualitative research. The data source used by the author is the premier data source